MANAJEMEN ANTARA UMAT BERAGAMA STUDI KASUS: UMAT BERAGAMA BUDHA DI TANJUNG BATU KECAMATAN KUNDUR KABUPATEN KARIMUN - Pipi Pipi (Horizon, 2021)
This study discusses the existence of the management of harmony between Islam and Buddhism in Tanjung Batu Kota. This study aims to describe the factors that cause religious harmony in Tanjung Batu Kota, Kundur District, Karimun Regency.This study used the conflict theory according to Lewis Coser. This research used a qualitative approach with a descriptive type. purposive sampling technique was used to select the informant that consists of 10 people. The types of data used in this study were primary data and secondary data. Observation, in-depth interviews, and document studies were used in collecting the data. Meanwhile, the data analysis unit used by the group was Milles and Huberman's data analysis, namely data collection, data reduction, data presentation, and conclusion drawing. The results of this study reveal that several factors are causing religious harmony: 1) Tolerance in the Economic Sector. 2) Inter-Religious Harmony. 3) Mutual Respect and Respect for Other Religions. 4) The Management of Religious Harmony in Tanjung Batu City, Kundur District.